2018
DOI: 10.4103/psychiatry.indianjpsychiatry_221_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in Punjab: Findings from National Mental Health Survey

Abstract: Background:Knowledge of the prevalence of mental disorders is essential for setting up services and allocation of resources. Existing studies suffer from methodological problems which limit their utility and generalizability. There was a long felt need to conduct a scientifically robust study in different regions of India to have national prevalence rates.Aims:This study aims to estimate the prevalence of mental disorders in a representative population of Punjab as a part of the National Mental Health Survey.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…In Punjab, the study was carried out by the Department of Psychiatry, Government Medical College and Hospital, Chandigarh. The detailed methodology of the study is available in ‘National Mental Health Survey of India, 2015-16: Prevalence, pattern and outcomes’ (Gururaj et al, 2016) and elsewhere (Chavan, Das, Garg, Puri, & Banavaram, 2018). In this article we briefly describe the methodology with specific emphasis on the assessment of disability and socio-economic impact associated with mental and substance use disorder in the state of Punjab.…”
Section: Methodsmentioning
confidence: 99%
“…In Punjab, the study was carried out by the Department of Psychiatry, Government Medical College and Hospital, Chandigarh. The detailed methodology of the study is available in ‘National Mental Health Survey of India, 2015-16: Prevalence, pattern and outcomes’ (Gururaj et al, 2016) and elsewhere (Chavan, Das, Garg, Puri, & Banavaram, 2018). In this article we briefly describe the methodology with specific emphasis on the assessment of disability and socio-economic impact associated with mental and substance use disorder in the state of Punjab.…”
Section: Methodsmentioning
confidence: 99%
“…The overall prevalence of at least one diagnosis on PHQ-9 is 13.45% and the prevalence is significantly higher in reverse migrants (19.3%) in comparison to the undisplaced migrants (7.6), and the prevalence of other depressive disorder is 10.55% and which is again significantly higher in reverse migrants (17.1%) than undisplaced migrants (4.0%). The findings of index study clearly show that the prevalence of mental health issues in the reverse migrants is significantly higher than general population (Chavan et al, 2018) and also higher than the earlier study on migrant population from Karnataka (Rock et al, 2016). The prevalence of depressive disorder (17.1%) in reverse migrants is significantly higher than the general population as well as another study on migrant population (Ismayilova et al, 2014).…”
Section: Discussionmentioning
confidence: 41%
“…DivinaKumar et al (2017) found that 41% of the industrial workers used tobacco. The findings of National Mental Health survey (Chavan et al, 2018) from Punjab showed that the prevalence of current mental morbidity was 13.42% in the general population, much less than the migrant population. Similarly, a recent national survey on the extent and pattern of substance abuse in the general population of India revealed that alcohol was the most common substance of abuse (14.6%), followed by cannabis (2.8%), opioids (2.1%), sedative-hypnotics (1.18%) and inhalants (0.7%) (Ambekar et al, 2019).…”
Section: Psychiatric Morbidity and Substance Use In Migrant Workers: A Population Based Studymentioning
confidence: 97%
“…Our searches identified three reports based on the Global Burden of Disease studies, which we excluded on the basis of study design (Baxter et al, 2016; Liu et al, 2020; Sagar et al, 2020), and because analyses were either limited to just India or estimated annual percentage change in the burden of depression across the region, not directly comparable to the results of our analyses. Similarly, three reviews (Reddy and Chandrashekar, 1998; Ganguli, 2000; Arora and Aeri, 2019) included in the Hossain et al (2020) umbrella review did not meet our eligibility criteria on study design, but those topics were covered in other included reviews. Our review includes all other reviews they included, but by going beyond geographically limited reviews and summarising the evidence from multi-country reviews that included at least one South Asian country, we have identified many more reviews, providing a more complete picture of the evidence regarding the prevalence of mental disorders in the region.…”
Section: Discussionmentioning
confidence: 99%